1999
DOI: 10.1017/s0022149x99000578
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adult liver flukes from highland and lowland populations of Bolivian and Spanish sheep

Abstract: A morphological study of adult liver flukes and eggs from sheep in a human fascioliasis endemic zone in the Northern Bolivian Altiplano showed that they belong to the species Fasciola hepatica. An exhaustive morphometric comparison with a F. hepatica population from Spanish sheep was made using image analysis and an allometric model: (y2m - y2)]#x002F;y2 = c[(y1m - y1)/y1]b, where y1 = body surface or body length, y2 = one of the measurements analysed, y1m, y2m = maximum values towards which y1 and y2 respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Multidisciplinary studies were undertaken to disentangle how the liver fluke and its lymnaeid snail hosts adapted to the extreme environmental conditions of the high altitude and succeeded in giving rise to high infection rates (MasComa et al 1999c). Intraspecific morphological variability studies showed no significant difference between F. hepatica adult flukes from Bolivia and Spain (Valero et al 1999). Snail anatomy and shell morphology , Samadi et al 1999, DNA sequencing Mas-Coma 1997, Bargues et al 1997) and isoenzymatic studies (JabbourZahab et al 1997) proved that Lymnaea truncatula (Müller, 1774) (Gastropoda: Basommatophora: Lymnaeidae) is the only intermediate host species in the Northern Bolivian Altiplano.…”
mentioning
confidence: 99%
“…Multidisciplinary studies were undertaken to disentangle how the liver fluke and its lymnaeid snail hosts adapted to the extreme environmental conditions of the high altitude and succeeded in giving rise to high infection rates (MasComa et al 1999c). Intraspecific morphological variability studies showed no significant difference between F. hepatica adult flukes from Bolivia and Spain (Valero et al 1999). Snail anatomy and shell morphology , Samadi et al 1999, DNA sequencing Mas-Coma 1997, Bargues et al 1997) and isoenzymatic studies (JabbourZahab et al 1997) proved that Lymnaea truncatula (Müller, 1774) (Gastropoda: Basommatophora: Lymnaeidae) is the only intermediate host species in the Northern Bolivian Altiplano.…”
mentioning
confidence: 99%
“…These changes may in¯uence the development of a liver¯uke such as F. hepatica, mainly because of its tissue migration and haematophagous diet (Dawes and Hughes 1964;Boray 1969). To ascertain whether geographic isolation and adaptation to high altitude have given rise to a parasite morph divergence (as detected in Altiplanic lymnaeid snails ± see Oviedo et al 1995), dierent morpho-anatomical aspects of liver¯uke adults additional to the characteristics already analysed by Valero et al (1999) are currently being studied. The aim of the present paper is to analyse the results obtained in the studies on uterus development.…”
Section: Introductionmentioning
confidence: 99%
“…In F. hepatica, Neuhaus (1978) has already showed that the length of the uterus in F. hepatica at dierent stages of development is correlated with the size of the body. In the present paper, a comparison is made with the equation described by Valero et al (1991Valero et al ( , 1996Valero et al ( , 1999. To analyse the in¯uence of host species on the development of the liver¯uke uterus at high altitudes, Bolivian Altiplanic liver¯uke populations from three dierent host species (sheep, cattle and pig) were studied.…”
Section: Introductionmentioning
confidence: 99%
“…To identify eggs from F. hepatica, the parameters described by Boray et al (1983) and Valero et al (1999) were considered. The samples were positive when containing at least one F. hepatica egg.…”
Section: Stool Analysismentioning
confidence: 99%